2005
DOI: 10.1109/tbme.2004.839636
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cardiac Rhythm Features by Mathematical Analysis of Vector Fields

Abstract: Automated techniques for locating cardiac arrhythmia features are limited, and cardiologists generally rely on isochronal maps to infer patterns in the cardiac activation sequence during an ablation procedure. Velocity vector mapping has been proposed as an alternative method to study cardiac activation in both clinical and research environments. In addition to the visual cues that vector maps can provide, vector fields can be analyzed using mathematical operators such as the divergence and curl. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Other techniques have been used to analyze HR cardiac mapping studies 10, 14, 35, 36 . However these methods could not be directly translated to the GI field due to the significantly different characteristics in the spatio-temporal patterns, time course and signals between cardiac and GI electrophysiology 9, 8 .…”
Section: Limitations Discussion and Conclusionmentioning
confidence: 99%
“…Other techniques have been used to analyze HR cardiac mapping studies 10, 14, 35, 36 . However these methods could not be directly translated to the GI field due to the significantly different characteristics in the spatio-temporal patterns, time course and signals between cardiac and GI electrophysiology 9, 8 .…”
Section: Limitations Discussion and Conclusionmentioning
confidence: 99%
“…Velocity estimation from the isochronal maps generated from HR mapping can provide a complimentary qualitative and quantitative view of the data on the slow wave propagation patterns, particularly in dysrhythmic states. Mathematical operations on the velocity vectors such as dot product, cross product, curl and divergence have been found to yield valuable information about the underlying electrical activity in cardiac electro-physiology [24]. In cardiology, it has been shown that the atrial electrogram fractionation [25], a feature in atrial fibrillation, occurs in regions of slow conduction.…”
Section: Discussionmentioning
confidence: 99%
“…The velocity was calculated using the following linear model (2) at each of the subset reference electrode grids [25] (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…This approach is computationally less intensive compared to the ptraditional approach and is able to quantitatively assess key parameters such as velocity and amplitude profiles of slow wave activity in a reliable manner, without manual intervention. Similar methods have been used in cardiac electrophysiology [2225], but this is the first time this method has been adapted and applied for GI HR slow wave recording analysis, requiring important modifications to account for multiple wavefronts in the mapped field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation